2018
DOI: 10.1002/eco.2053
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic responses to climate warming for a snow‐dominated watershed and a transient snow watershed in the California Sierra

Abstract: Climate warming will have substantial impacts on hydrological fluxes in the California Sierra. A commonly used approach for assessing these impacts, particularly in mountain watersheds, is to substitute space for time. This conceptual model assumes that with warming, the hydrologic behaviour of higher elevation snow dominated watersheds (SDWs) will converge to the hydrologic behaviour of lower elevation transient snow watersheds (TSWs). To investigate the efficacy of this conceptual model, a process‐based mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 42 publications
5
24
0
Order By: Relevance
“…RHESSys has been used for hydrologic simulations in a variety of environments (Bart et al, 2016; Christensen et al, 2008; Grant et al, 2013; Hartman et al, 1999; Jefferson et al, 2008; Son, 2015; e.g., Tague & Grant, 2009; Tague & Peng, 2013; Tague et al, 2007, 2009, 2013). Numerous studies have evaluated RHESSys estimates of ecohydrologic fluxes in seasonally water‐limited Mediterranean environments by comparison with a broad set of relevant observations, including streamflow (Boisramé et al, 2019; e.g., Tague & Peng, 2013), snowmelt (Son & Tague, 2018), ET (Tague & Moritz, 2019; Zierl et al, 2007), interannual variation in tree rings (Vicente‐Serrano et al, 2015), and leaf‐scale conductance measurements (Tsamir et al, 2019). These comparisons suggest that RHESSys accurately represents the dominant controls on seasonal and interannual variation in ET for these systems.…”
Section: Methodsmentioning
confidence: 99%
“…RHESSys has been used for hydrologic simulations in a variety of environments (Bart et al, 2016; Christensen et al, 2008; Grant et al, 2013; Hartman et al, 1999; Jefferson et al, 2008; Son, 2015; e.g., Tague & Grant, 2009; Tague & Peng, 2013; Tague et al, 2007, 2009, 2013). Numerous studies have evaluated RHESSys estimates of ecohydrologic fluxes in seasonally water‐limited Mediterranean environments by comparison with a broad set of relevant observations, including streamflow (Boisramé et al, 2019; e.g., Tague & Peng, 2013), snowmelt (Son & Tague, 2018), ET (Tague & Moritz, 2019; Zierl et al, 2007), interannual variation in tree rings (Vicente‐Serrano et al, 2015), and leaf‐scale conductance measurements (Tsamir et al, 2019). These comparisons suggest that RHESSys accurately represents the dominant controls on seasonal and interannual variation in ET for these systems.…”
Section: Methodsmentioning
confidence: 99%
“…Ecohydrological fluxes incorporated in RHESSys, e.g., streamflow, evapotranspiration, and net primary productivity under climate change, can provide crucial data to support watershed sustainable management under climate change. For example, Son et al [31] examined the shift in snowmelt, runoff, and evaporation between a snow-dominated basin and rainfall-dominated watershed under projected global warming of 2 or 4 • C, California, USA. Besides, they identified that vegetation structures and soil properties are also crucial factors for ecohydrological responses to climate change.…”
Section: Climate Changementioning
confidence: 99%
“…Previous studies have often estimated and calibrated the snow-related parameters based on R 2 (determination coefficient) for snow depth, a snow-water equivalent. For example, Son et al conducted the calibration of snow-related parameters by comparing measured snow depth data and modeled snow-water equivalent, which results in an R 2 of 0.87 and 0.70, implying that the model reproduced the real snowmelt process [31,37]. For studies that require detailed ecological outputs, vegetation-related parameters are manually calibrated with remote sensing or field-observed Leaf Area Index (LAI) data [18,38].…”
Section: Calibrationmentioning
confidence: 99%
See 2 more Smart Citations